2011
DOI: 10.1007/s10725-011-9644-4
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine and ethylene interactions in grain filling of superior and inferior spikelets of rice

Abstract: This study was to test the hypothesis that polyamines (PAs) and ethylene and their interactions may be involved in mediating the post-anthesis development of spikelets in rice (Oryza sativa L.). Six rice cultivars differing in grain filling rate were field-grown, and the changing patterns of PAs and ethylene levels in rice spikelets during the filling and their relations with grain filling rates were investigated. The results showed that inferior spikelets had much greater ethylene evolution rate and 1-aminocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 43 publications
6
47
0
Order By: Relevance
“…Furthermore, SD down-regulated TaSUT1 expression, but increased the WSC content at 14 and 21 DPA. These alternations in WSC content and TaSUT1 expression combined with the strongly decreased activities of SuS ase , AGP ase , and SSS ase under SD confirmed that the starch biosynthesis enzymes activities, rather than photo-assimilate supply, were a major constraint on grain filling at the middle-filling stage, which concurs with previous reports1535. The results also indicated a large difference in the decrease of grain weight between different kernel positions of wheat spikelets736, 7.38 and 23.5% for superior and inferior grains, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, SD down-regulated TaSUT1 expression, but increased the WSC content at 14 and 21 DPA. These alternations in WSC content and TaSUT1 expression combined with the strongly decreased activities of SuS ase , AGP ase , and SSS ase under SD confirmed that the starch biosynthesis enzymes activities, rather than photo-assimilate supply, were a major constraint on grain filling at the middle-filling stage, which concurs with previous reports1535. The results also indicated a large difference in the decrease of grain weight between different kernel positions of wheat spikelets736, 7.38 and 23.5% for superior and inferior grains, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Application of ethylene inhibitors increased grain weight in wheat5 and improved dry matter partitioning and grain filling of basal rice kernels14, whereas ethephon (an ethylene-releasing agent) application showed the opposite effect. ACC concentration plays a decisive role in the ethylene evolution rate15 and its synthase gene ( ACS ) is present in all wheat tissues, especially during the early stages of spike development16. Based on the spatial position in wheat spikes, kernels at the base of the spikelets are regarded as superior grains, whereas the distal kernels are considered as inferior grains17.…”
mentioning
confidence: 99%
“…The promotive effects of PAs on post-anthesis development of rice were demonstrated by Tan et al (2009) who found that the grain filling rate and brown rice weight were highly correlated with endogenous Spd and Spm concentration in developing grains in six rice cultivars. Wang et al (2012) also found that endogenous Spd and Spm concentrations in the developing panicles were positively correlated with the grain filling rate but negatively correlated with ethylene evolution rate. In developing maize grains, Cao et al (2010) demonstrated that Spd concentration has much higher positive correlations with seed weight and quality than Put and Spm.…”
Section: Discussionmentioning
confidence: 73%
“…Many factors, such as assimilation supply, hormonal balance (Yang et al, 2006; Zhang et al, 2009; Yang and Zhang, 2010), and activities and gene expressions of key enzymes involved in sucrose-to-starch conversion (Jeng et al, 2003; Ishimaru et al, 2005; Kato et al, 2007; Wang et al, 2012), are involved in mediating the grain-filling of inferior spikelets. Most studies have shown that the low activities of key enzymes in carbon metabolism rather than carbon limitation mainly contribute to the poor grain-filling of inferiors because their enzyme activities are markedly lower (Yang J.C. et al, 2001; Yang et al, 2002; Tao et al, 2003), whereas the poor fertility in inferior spikelets may be associated with a lack of assimilates (Wang et al, 2001; Tao et al, 2003; Kobata et al, 2013).…”
Section: Introductionmentioning
confidence: 99%